2017
DOI: 10.18203/2349-2902.isj20175482
|View full text |Cite
|
Sign up to set email alerts
|

Conventional treatment versus vacuum therapy for diabetic foot ulcers treatment

Abstract: Background: This study compares the efficacy of vacuum therapy against conventional iodine povidone dressing with respect to area and time of ulcer.Methods: This study is a randomized controlled trail which was conducted in Meenakshi Medical College hospital and research institute Enathur Kanchipuram. The number of patients selected were 50, which were divided into 2 groups, Group A which consisted of 25 and received vacuum therapy, Group B which consisted of 25 and received povidone-iodine solution.Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…At this stage, we applied NPWT to enhance wound healing by increasing local blood flow, reducing tissue edema, eliminating exudates, promoting cell hyperplasia, and preventing bacterial growth [7]. Similar to our report, some recent studies have also confirmed that NPWT is a safe and effective technique to accelerate wound healing [18,19]. AMG was another modern therapy that we combined with conventional treatment.…”
Section: Discussionsupporting
confidence: 79%
“…At this stage, we applied NPWT to enhance wound healing by increasing local blood flow, reducing tissue edema, eliminating exudates, promoting cell hyperplasia, and preventing bacterial growth [7]. Similar to our report, some recent studies have also confirmed that NPWT is a safe and effective technique to accelerate wound healing [18,19]. AMG was another modern therapy that we combined with conventional treatment.…”
Section: Discussionsupporting
confidence: 79%
“…Conventional methods alone sometimes fail to heal chronic ulcers so that adjunctive methods may be necessary. 4 Hyperbaric oxygen therapy (HBOT) has been proposed to aid treatment of DFUs owing to its effects on the reversal of wound tissue hypoxia. 5 Administering 100% oxygen at 1 absolute atmospheric air (ATA) pressure for a period of time increases the amount of oxygen dissolved in the plasma 5-fold; from 0.3 to 1.5 ml/L 3 , and at 2.5 ATA, the dissolved oxygen content is approximately 5.5 ml/L 3 .…”
mentioning
confidence: 99%
“…Conventional methods alone sometimes fail to heal chronic ulcers so that adjunctive methods may be necessary. 4…”
mentioning
confidence: 99%
“…These factors result in longer time taken to heal and reduce the tensile strength of the wound. 3 In diabetes mellitus, there are numerous derangements such as ischemia, neuropathy, microangiopathy, impaired immunity and defective angiogenesis. 4 During hyperglycemia, free radicals also increase which often leads to damage to blood vessels, accelerated atherosclerosis, diabetic nephropathy, neuropathy and retinopathy.…”
mentioning
confidence: 99%
“…They further get infected leading to cellulitis, necrosis and formation of diabetic wound. 3 Old age, poor glycemic control, diabetic neuropathy, previous history of amputation or ulcers are all risk factors for diabetic ulcers. 3 Ulcers can be prevented by good glycemic control, detailed examination and proper foot care.…”
mentioning
confidence: 99%